2014
DOI: 10.1074/jbc.m113.506246
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxypropyl-β-cyclodextrin Promotes Transcription Factor EB-mediated Activation of Autophagy

Abstract: Background:The drug delivery vehicle 2-hydroxypropyl-␤-cyclodextrin (HP␤CD) prevents cholesterol storage. Results: HP␤CD treatment induces TFEB mediated activation of autophagy and clearance of the autophagic substrate ceroid lipopigment. Conclusion: HP␤CD administration results in enhancement of the innate autophagic clearance capacity. Significance: Dissecting the cellular pathways impacted by HP␤CD is crucial to design HP␤CD-based therapeutic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 57 publications
(62 reference statements)
6
91
0
Order By: Relevance
“…A predominantly nuclear localization of TFEB was observed in fibroblasts from mouse models of different lysosomal storage disorders, suggesting that the lysosome-autophagy system is modulated at the transcriptional level in response to lysosomal storage [11]. Modulation of TFEB activation was also observed upon cellular uptake of 2-hydroxypropyl-beta-cyclodextrin [12], quantum dots [13], and polystyrene nanoparticles [14], suggesting that transcriptional modulation of autophagy is part of the cellular adaptative response to nanomaterials.…”
Section: The Autophagy Pathwaymentioning
confidence: 82%
See 1 more Smart Citation
“…A predominantly nuclear localization of TFEB was observed in fibroblasts from mouse models of different lysosomal storage disorders, suggesting that the lysosome-autophagy system is modulated at the transcriptional level in response to lysosomal storage [11]. Modulation of TFEB activation was also observed upon cellular uptake of 2-hydroxypropyl-beta-cyclodextrin [12], quantum dots [13], and polystyrene nanoparticles [14], suggesting that transcriptional modulation of autophagy is part of the cellular adaptative response to nanomaterials.…”
Section: The Autophagy Pathwaymentioning
confidence: 82%
“…The ability of 2-hydroxypropyl-beta-cyclodextrin, an FDA-approved excipient used to enhance drug stability and bioavailability, to induce autophagic clearance was demonstrated in in vitro model systems characterized by aberrant accumulation of distinct biological materials [12,44]. Interestingly, 2-hydroxypropyl-beta-cyclodextrin-mediated activation of TFEB was found not to depend on its ability to alter cellular levels of cholesterol [44].…”
Section: Activation Of Autophagic Clearancementioning
confidence: 96%
“…Lysosome-related genes are reported to be closely regulated in the orbital fat of patients suffering from Graves' ophthalmopathy, whereas down-regulation of lysosomal processing improved pegylated lipopolyplex-mediated gene transfection (51,52). The increase in lysosomal biogenesis may not necessarily prove to be beneficial in all disease and cell types, but in some cases induction of the autophagy-lysosomal pathway could be helpful for cellular clearance of toxic wastes (53,54). Over the past few years, TFEB has emerged as a potential therapeutic target for some lysosome-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, not many therapeutically viable compounds targeting TFEB activity have been identified. Recently, it has been shown that 2-hydroxypropyl-␤-cyclodextrin, an FDA-approved excipient, promotes TFEB-mediated clearance of proteolipid aggregates in cells from patients suffering from LINCL (54). Another study reveals induction of TFEB levels and activity as well as lysosomal biogenesis by genistein (5,7-dihydroxy-3-(4-hydroxyphenyl)-4H-1-benzopyran-4-one), a potential drug for the use in substrate reduction therapy for mucopolysaccharidoses (60).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it will be important to determine if βCDs trigger a transcriptional program that primes RPE cells to eliminate its lysosomal content, independently on whether they form soluble complex with the wasted material. Similarly, ibroblasts from patients with ceroid-lipofuscinosis, the most common cause of neurodegeneration of children in the United States, and cellular or animal models with misfolded α-synuclein accumulation were cleared by βCDs [132,133]. The mechanism in these cases seemed to be mediated by TFEB [86,134].…”
Section: Beta-cyclodextrins (β-Cds)mentioning
confidence: 99%